When Does Ethical Leadership Affect Workplace Incivility? The Moderating Role of Follower Personality - Taylor, Shannon G. (Business ethics quarterly, 2014)
Although prior work has shown that employees with ethical leaders are less likely to engage in deviant or unethical behaviors, it is unknown whether all employees respond this way or to the same extent. Drawing on social learning theory as a conceptual framework, this study develops and tests hypotheses suggesting that two follower characteristics—conscientiousness and core self-evaluation—moderate the negative relationship between ethical leadership and workplace incivility. Data from employees of a U.S. public school district supported our predictions. Implications and future research directions are discussed.